Intragenomal Distribution of DNA Repair Synthesis: Repair in Satellite and Mainband DNA in Cultured Mouse Cells - Lieberman, Michael W. (1974)
DNA repair synthesis was examined in mouse satellite and mainband DNA derived from confluent Balb/c 3T3 cells damaged with ultraviolet radiation or N-acetoxy-2-acetylaminofluorene. Two different approaches were used: (i) Contact-inhibited cells were treated with hydroxyurea to reduce replicative synthesis to low levels; and (ii) bromodeoxyuridine was used to label newly replicated DNA in cells that had escaped contact inhibition. DNA was separated into mainband and satellite fractions in Ag(+)-Cs(2)SO(4) gradients. After treatment with either ultraviolet radiation or N-acetoxy-2-acetylaminofluorene, repair synthesis occurred to the same extent in mainband and satellite DNA. Repair synthesis increased over an ultraviolet radiation dose range of 30-200 erg/mm(2), and the extent of repair in the two DNA species was similar at each dose level. An analysis of the separated strands of satellite DNA from ultraviolet-irradiated cells indicated that the extent of repair is closely correlated with the availability of pyrimidines for cyclobutyl dimer formation and provided evidence that repair synthesis occurs at the site of damage. Within the precision of our experiments the results suggest that at least one group of highly repetitive, nontranslated DNA sequences is repaired to about the same extent as the rest of the genome.